Pengaruh Proses Pendidikan Di Aal Terhadap Kemampuan Kepemimpinan Lapangan Perwira Remaja Di Tempat Penugasan Dengan Performance Sebagai Variabel Intervening - Dian Tri Hutanto; Prasetyo Hadi (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
Some researches of education elements have been greatly worked out in the educational institutions, yet the researches have been rarely conducted in Indonesian Military Training Institutions. This research is aimed to prove that there is a positive influence of the Indonesian Naval Academy training process on the junior officer’s field leadership ability as the Indonesian Naval Academy graduates. And this research is particularly to prove that the performance of junior officers as resulted from Indonesian Naval Academy training is capable of being an intervening variable between the training and the ability of field leadership. The populations of this research are junior officers graduated from Indonesian Naval Academy in 2009, 2010 and 2011 serving in eastern fleet and 1st Marine Division. The method of sampling is a proportional simple random sampling by 132 samples. The complexity of interrelation occurred   between variables make variant of Partial Least Square based Structural Equation Modeling as a mean to prove a proposed hypotesa. The eventual conclusions are that educational variable in Indonesian Naval Academy has positive and significant influences on junior officer’s performances; performance variable has positive and significant influences on the ability of field leadership; educational variable has positive and significant influences on the ability of field leadership; field performance as previously played a role as intervening variable (between) has changed the role to be a moderating variable (amplifying), and the ability of junior officer’s field leadership in the workplace will be better if it is achieved from indirect interrelation between educational variable in Indonesian Naval Academy and the ability of junior officer’s field leadership with moderating performance variable in the workplace.